Particles : an introduction to particle physics - Chester, Michael. 4 0 16; 5 (New York : Macmillan, 1978)
An introduction to the world of atomic and sub-atomic particles, including positions, kaons, anti-protons, quarks, and others.
Includes index.
Keywords: 2 -- 0; 6; Juvenile literature. -- Particles (Nuclear physics);Particles (Nuclear physics);Nuclear physics. -- 20; 20; 2